Blended Learning Model Based on Massive Open Online Courses (MOOCs) Assisted by Augmented Reality (BMA) Model as the Electronic Learning Media in the Pandemic Covid-19 - Eko Risdianto; Wachidi Wachidi; Riyanto Riyanto; Alexon Alexon; Irwan Fathurrochman; Kusen Kusen (STAI Hubbulwathan Duri, 2021)
This study aims to analyze educators' responses to implementing the blended learning model based on MOOCs assisted by augmented reality or the so-called BMA model. This BMA model is applied to the learning process using the MOOCs system that has been developed with augmented reality assistance in the midst of the COVID-19 pandemic. To determine the response of prospective educators in the study, data collection techniques were carried out using a questionnaire given to 47 students. This questionnaire consists of 17 question items with 4 Likert scales. The data analysis technique used qualitative, quantitative data analysis. To test the quality of the questionnaire given, data analysis was used using the Rasch model and the winsteps application. Based on the research results, it was found that the instrument data used were valid and reliable. The results of student responses obtained are in very good criteria. This is reinforced by the results of the validity calculation in the rasch analysis which was carried out which stated that 17 items were declared valid and no items were issued. In addition, the value of the calculation of data reliability using the alpha cronbach method with a score of 0.91 is higher than the r table value for α = 0.05 0.2876. Thus it can be said that the data used is reliable and prospective educators respond very well to the use of this BMA model in the implementation of the learning process through the MOOCs system during the Covid-19 pandemic. This is reinforced by the results of the validity calculation in the rasch analysis which was carried out which stated that 17 items were declared valid and no items were issued. In addition, the value of the calculation of data reliability using the alpha cronbach method with a score of 0.91 is higher than the r table value for α = 0.05 0.2876. Thus it can be said that the data used is reliable and prospective educators respond very well to the use of this BMA model in the implementation of the learning process through the MOOCs system during the Covid-19 pandemic. This is reinforced by the results of the validity calculation in the Rasch analysis, which was carried out, which stated that 17 items were declared valid and no items were issued. In addition, the value of the calculation of data reliability using the alpha cronbach method with a score of 0.91 is higher than the r table value for α = 0.05 0.2876. Thus, the data used is reliable, and prospective educators respond very well to the use of the BMA model in the implementation of the learning process through the MOOCs system during the Covid-19 pandemic.